Perilaku Impulse Buying Sebagai Dampak Hedonic Shopping Motivation Dan Shopping Lifestyle Case Study On Tiktok Shop Feature Users In The City Of Bandung - Sondari, Tanty; Pratama, Roro Arinda Reswanti Julian; Johan, Ahmad; Fitriana, Nahda (Universitas Gorontalo, 2024)
Information technology in Indonesia has experienced significant growth with the emergence of e-commerce and social commerce as platforms for online sales transactions. One of the leading social commerce platforms in Indonesia is TikTok Shop. It is no wonder that consumers in Bandung use TikTok Shop as a venue for online sales and transactions. Promotions, offers, and free shipping provided by TikTok Shop, along with its user-friendly interface, can foster hedonic shopping tendencies, supported by a shopping lifestyle that disregards whether the purchased product is needed or not, and involves impulse buying during window shopping. This study aims to determine the extent to which Hedonic Shopping Motivation and Shopping Lifestyle influence Impulse Buying Behavior among TikTok Shop users in Bandung. The population of this study includes all consumers using TikTok Shop who reside in Bandung. This research employs a quantitative approach with descriptive analysis. The sampling technique used is Purposive Sampling, targeting TikTok Shop users living in Bandung. Data analysis is conducted using multiple linear regression analysis. The results of this study indicate that Hedonic Shopping Motivation has a positive and significant influence on impulse buying behavior, and Shopping Lifestyle also has a positive and significant influence on impulse buying behavior. Moreover, Hedonic Shopping Motivation and Shopping Lifestyle together have a positive and significant influence on impulse buying behavior.